2015
DOI: 10.1109/tdmr.2015.2424151
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered ALD HfAlO<sub>x</sub> and HfO<sub>2</sub> for High-Quality Gate Stacks

Abstract: This paper has demonstrated a high-quality HfO 2based gate stack by depositing atomic-layer-deposited HfAlO x along with HfO 2 in a layered structure. In order to get a multifold enhancement of the gate stack quality, both Al percentage and distribution were observed by varying the HfAlO x layer thickness and its location in the gate stack. It was found that < 2% Al/(Al + Hf)% incorporation can result in up to 18% reduction in the average EOT along with up to 41% reduction in the gate leakage current, as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…It can be clearly observed that the trapping level gradually changes from 0.66 eV to 0.77 eV with increasing the CL thickness up to 2nm. The deeper trapping level of 0.77 eV is mainly ascribed to the effect of AlO x CL, which not only reduces the shallow traps near TaN/HfZrO x interface [27], [28], but also enhances the thermal stability of HfZrO x MFM capacitor. Therefore, the AlO x CL effectively improves interface quality to eliminate the interface shallow traps, possibly causing charge trapping/detrapping and domain wall pining during ferroelectric switching.…”
Section: Resultsmentioning
confidence: 99%
“…It can be clearly observed that the trapping level gradually changes from 0.66 eV to 0.77 eV with increasing the CL thickness up to 2nm. The deeper trapping level of 0.77 eV is mainly ascribed to the effect of AlO x CL, which not only reduces the shallow traps near TaN/HfZrO x interface [27], [28], but also enhances the thermal stability of HfZrO x MFM capacitor. Therefore, the AlO x CL effectively improves interface quality to eliminate the interface shallow traps, possibly causing charge trapping/detrapping and domain wall pining during ferroelectric switching.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability of semiconductor products has helped this industry to enjoy stable growth. The reliabilities of transistors and their gates are treated with high importance in semiconductor fabrication [35]. Now, the reliability of battery and lifetime modeling is also drawing attention [36].…”
Section: Problem Definitionmentioning
confidence: 99%
“…With the desired goal of reducing cell-to-cell variation, the focus has to be on the contributing factors that are responsible for the process variation. Analytical expression presented by Sikha et al [56], and the resistance and capacitance models of Shin et al [35] provide insight into the battery performance. This model can be used to further breakdown and identify the key contributors to cell properties, as shown in Figure 5 [38].…”
Section: Modifying Process Mechanismmentioning
confidence: 99%
“…These properties cause a significant increase in the leakage current if HfO 2 films are incorporated in a high-temperature MIS system. To increase the crystallization temperature and enhance the electrical properties of HfO 2 , it can be converted to alloy HfAlO x (hafnium aluminum) using aluminum oxide (Al 2 O 3 ) intermixed [19][20][21]. Furthermore, the integration of the Al into HfO 2 causes an increase in its dielectric constant and bandgap as well as decreases its hysteresis and charging defects.…”
Section: Introductionmentioning
confidence: 99%